The Oral Epic of Ngombi Nliga Ngwan: Between Literariness and Pragmatics - Mahop Ma Mahop, Romuald-Achille (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This essay studies an oral epic from the Basaa of Cameroon, transcribed, translated into French and annotated recently for the first time (2019). Resorting to an interdisciplinary methodology that combines contributions from anthropology, stylistics and literary pragmatics, the reflection attempts to underline the literary nature of of the peak story, which not only brings together the fundamental traits commonly accepted as literary ones of the peak genre, but also lends itself to the theories developed in recent decades within the framework of the aesthetics of the reception. Thus, the text is inserted in its enunciative context and certain sociological and axiological values typical of the Cameroonian Basaa socioculture are emphasized.